2016
DOI: 10.1016/j.cognition.2016.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Language and memory for object location

Abstract: In three experiments, we investigated the influence of two types of language on memory for object location: demonstratives (this, that) and possessives (my, your). Participants first read instructions containing demonstratives/possessives to place objects at different locations, and then had to recall those object locations (following object removal). Experiments 1 and 2 tested contrasting predictions of two possible accounts of language on object location memory: the Expectation Model (Coventry, Griffiths, & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 51 publications
3
34
0
Order By: Relevance
“…
Figure 2 . The participant reads out the instruction card, then memorizes the object location and finally instructs the experimenter to move the indication stick and align it with where the edge of the object was 14 . Please click here to view a larger version of this figure.…”
Section: Introductionmentioning
confidence: 99%
“…
Figure 2 . The participant reads out the instruction card, then memorizes the object location and finally instructs the experimenter to move the indication stick and align it with where the edge of the object was 14 . Please click here to view a larger version of this figure.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to language and linguistic structure, both written and spoken, modulates cognitive functions that have hitherto been considered non-linguistic (Athanasopoulos et al, 2015;Boiteau & Almor, 2017;Chatterjee, Southwood, & Basilico, 1999;Coventry, Griffiths, & Hamilton, 2014;Dobel, Diesendruck, & Bölte, 2007;Fuhrman & Boroditsky, 2010;Gudde, Coventry, & Engelhardt, 2016;Hendricks & Boroditsky, 2017;Kranjec, Lehet, Bromberger, & Chatterjee, 2010;Levinson, 2003;A Maass & Russo, 2003;Román, El Fathi, & Santiago, 2013;Stroustrup & Wallentin, 2018;Tylén, Weed, Wallentin, Roepstorff, & Frith, 2010;Winawer et al, 2007).…”
Section: Left-right Bias In Imagery Caused By Readingmentioning
confidence: 99%
“…Experimental evidence has shown that this distinction does not encode purely metric distance between the speaker and the referent. In single-referent contexts, the contrast between proximal and distal demonstratives maps onto the functional distinction between peripersonal and extrapersonal space, that is, between space within and outside reach (Caldano & Coventry, in press;Coventry, Griffiths, & Hamilton, 2014;Coventry, Valdés, Castillo, & Guijarro-Fuentes, 2008;Gudde, Coventry, & Engelhardt, 2016). However, when multiple competing referents are present, their relative distance also matters when speakers choose between proximal and distal demonstratives (Bonfiglioli, Finocchiaro, Gesierich, Rositani, & Vescovi, 2009;Rocca, Wallentin, Vesper, & Tylén, 2018).…”
Section: Demonstratives Usage Patterns Reflect Functional Encoding Ofmentioning
confidence: 99%
“…Demonstratives provide indications on the position of objects (or locations) relative to the position of the speaker and conversational dyad (Coventry et al, 2014(Coventry et al, , 2008Gudde et al, 2016;Peeters et al, 2015). It is therefore crucial that the two speakers in the dialogue are assigned specific and distinct spatial origins.…”
Section: Present Study: Experimental Paradigmmentioning
confidence: 99%